2021
DOI: 10.2147/copd.s284397
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Azithromycin Maintenance Treatment in Patients with Frequent Exacerbations of Chronic Obstructive Pulmonary Disease

Abstract: Macrolides are effective in reducing the number of exacerbations in COPD patients with the frequent exacerbator phenotype. Our study did not show a persistent effect of azithromycin on exacerbation frequencies after more than one year of usage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Unfortunately, there were limited randomized controlled trials exploring the usage of macrolides for more than 12 months in COPD patients. A recent retrospective cohort study, following the COLUMBUS study, found no statistically significant difference between the group that received macrolides for 24 months and the group that received macrolides for 12 months before discontinuation [48]. Nevertheless, other retrospective studies have shown that the use of azithromycin 500 mg three times a week for 36 months reduced hospitalizations by 39% in COPD patients experiencing frequent exacerbations [49].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there were limited randomized controlled trials exploring the usage of macrolides for more than 12 months in COPD patients. A recent retrospective cohort study, following the COLUMBUS study, found no statistically significant difference between the group that received macrolides for 24 months and the group that received macrolides for 12 months before discontinuation [48]. Nevertheless, other retrospective studies have shown that the use of azithromycin 500 mg three times a week for 36 months reduced hospitalizations by 39% in COPD patients experiencing frequent exacerbations [49].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of antibiotics and systemic steroids reduced in-hospital mortality and lowered the risk of readmission within 30 days. 9 The latest GOLD guideline 2022, 3 British Thoracic Society guideline 2020, 31 and several studies 32 , 33 suggest using low-dose macrolide therapy in patients with COPD in the following scenarios: (1) patients with more than three exacerbations per year requiring steroid therapy and (2) patients who had at least one exacerbation requiring hospital admission per year. Low-dose macrolide therapy can also be considered for a minimum duration of six months and up to 12 months to assess the impact on exacerbation rate.…”
Section: Discussionmentioning
confidence: 99%